The tombs of Atuan - Le Guin, Ursula K., 1929- (Le Guin, Ursula K., 1929- Earthsea cycle, 2012)
Arha's isolated existence as high priestess in the tombs of Atuan is jarred by a thief, wizard Ged Sparrowhawk, who seeks a special treasure.